Passado e presente: uma análise dos determinantes da mortalidade entre idosos com base nos dados da SABE 2000-2006 - Marilia Miranda Forte Gomes (2011)
Currently, the elderly are the most growing population group in the world, particularly in developing countries. Beyond of aging process of the population age structure, mainly due to the continued decline of fertility rates have also been observed both in the developed countries as in developing countries, significant reductions in mortality among the elderly. Accordingly with this premise many studies about mortality determinants in the population with 60 and over are more focused.In this way, this dissertation has three main goals: (i) review for the population with 60 and over, the association between mortality and marital status, controlling for variables that represent health conditions, socioeconomic status and lifestyle; (ii) to estimate mortality rates, according to education level, and evaluate the effect of education on mortality in the elderly, and (iii) to identify a possible relationship between socioeconomic status and health in childhood and mortality in older ages. To achieve the proposed goals, it was used the information from the SABE Study (Health, Welfare and Aging) 2000-2006 realized in São Paulo. The statistical analysis was performed based on Poisson regression models that take in consideration the estimated time of exposure to risk of death (person-years). The results confirmed the importance of be married to the long life of men and women and suggest that both selection mechanisms of protection are as important to analyze the differential mortality by marital status among the elderly living in São Paulo. Among elderly men, it was found that being single has remained afactor independently associated with mortality. In turn, the transition out ofmarriage, through the separation / divorce or widowhood, appears to increase the risk of death in older women analyzed. As observed in several developed countries, there has also been analyzed in the sample is that the higher the education level of the elderly, the lower mortality rates, regardless of sex. By decomposing the total effect of education on mortality, it was found that this relationship is mainly due to intermediary factors (66%), whose participation is most represented by risk behaviors (46%). Finally, it is observed that in large xx measure, the association between childhood conditions and mortality in old age is attenuated by socio-economic and lifestyle acquired in adulthood. It is hoped that the findings of this report can contribute to a better understanding of the factors associated with survival of the elderly, in addition to supportinghealth policies and inequality at this population group.